Fraud Diamond Model Dalam Mendeteksi Kecurangan Laporan Keuangan Perusahaan BUMN - Safanti, Shalsadila; Isyfa Fuhrotun Nadhifah (Forum Kerjasama Pendidikan Tinggi, 2025)
Financial statement fraud is a serious problem that can undermine accountability and public trust in state-owned enterprises (SOEs). This phenomenon is often caused by internal factors within the company, as explained in the fraud diamond theory, which includes pressure, opportunity, rationalization, and capability. This study aims to empirically test the influence of these four elements on the potential for financial statement fraud in SOEs during the period 2020–2023. The study uses a quantitative approach with multiple linear regression analysis on secondary data consisting of financial statements and fraud risk indicators from 25 SOEs selected purposively. The results indicate that pressure has a positive and significant effect with a regression coefficient of 0.312 (p = 0.004), opportunity with 0.289 (p = 0.009), and capability with 0.266 (p = 0.012) on financial statement fraud. Meanwhile, rationalization did not have a significant effect (p = 0.278). The regression model in this study had an R² value of 0.52, indicating that 52% of the variation in financial statement fraud could be explained by the four fraud diamond variables. These findings indicate that the pressure experienced by individuals, systemic opportunities within the organization, and the perpetrator's capabilities are dominant factors that increase the risk of fraud. Therefore, strengthening internal control systems, managing workloads, and promoting professional ethics are key strategies in preventing fraud within state-owned enterprises.